Impact of diabetes on long-term survival in elderly liver cancer patients: A retrospective study - Chen Dan; Gao Xiaoxiao; Wang Yaqing (Open Medicine)
Liver cancer is a prevalent and life-threatening condition, particularly among elderly individuals. The association between diabetes, a chronic metabolic disorder, and the onset and advancement of liver cancer has been widely acknowledged. However, the effect of diabetes on the survival of older patients with liver cancer has been a topic of debate. In light of this, we undertook a retrospective study to assess the impact of diabetes on the overall survival (OS) of elderly individuals diagnosed with liver cancer.